Wavelet Spatio-Temporal Change Detection on Multitemporal SAR Images - Fonseca, Rodney V.; Negri, Rogerio G. [UNESP]; Pinheiro, Aluisio; Atto, Abdourrahmane Mahamane (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In this article, we introduce the wavelet energies correlation screening (WECS), an unsupervised method to detect spatio-temporal changes on multitemporal SAR images. The procedure is based on wavelet approximation for the multitemporal images, wavelet energy apportionment, and ultrahigh-dimensional correlation screening for the wavelet coefficients. We show WECS's performance on simulated multitemporal image data. We also evaluate the proposed method on a time series of 85 Sentinel-1 images of a forest region at the border of Brazil and French Guiana. Comparisons with well-known change detection methods found in the literature highlight the proposal's superiority in terms of change detection accuracy. Additionally, the introduced method has simple architecture and low computational cost.
Keywords: Change detection; multitemporal images; remote sensing; simulated images; wavelets